Socio-Economic Implications of the Changing Expenditure Pattern of Farm Families in Punjab: A Case Study. - Sukhdev Singh & Suman Kumari (2005)
This study of changes in income levels and expenditure patterns of different categories of farm families of Punjab has indicated that medium and large families show a greater change in their income levels than others. Again these categories have shown the maximum change in their expenditure on socio-religious ceremonies, education and domestic services while small and marginal categories have shown greater change in expenditure on socio-religious ceremonies, fuel and furnishing the house. On food items, all categories of farm families have shown a change in the expenditure on meat, fish, eggs and miscellaneous food items like noodles, chips, chocolates, etc., indicating a significant change in the eating habits and tastes of the people. Price-hike, increasing demands of the children, social prestige and status, private schooling of children, rituals and weddings were significant factors in bringing about changes in the expenditure pattern. Shunning the habit of ostentation, following affordable schooling of the children, use of home-made nutritious food can save the farmers from future economic adversities.